"Post-stroke rehabilitation using mirror therapy" / Adi Mustakim Ab Rahim, Aiman Zharif Mohd Rahim and Muhammad Zulhairi Kamarulzailan - Ab Rahim, Adi Mustakim; Mohd Rahim, Aiman Zharif; Kamarulzailan, Muhammad Zulhairi (2019)
Mirror therapy is therapy that helps to create reflection illusion to trick the brain to think that the hand is having movement. This therapy tricks the brain into thinking that the affected hand moves in the same way as those who are not affected. It is also helping the brain to reorganize itself through a phenomenon known as neuroplasticity. Neuroplasticity is the brain's incredible ability to form a new neural connection based on environmental experiences. Our business consists of 3 partners where each partner holds a share in the company and contributed in certain number of percentages for company capital. Our main product is designed to post stroke patient. This product has many advantages for the post stroke patients because it is user friendly. This therapy also can do at home. This price that offered is affordable to all the customer.